Stereospecific route to 5,11-methanomorphanthridine alkaloids via intramolecular 1,3-dipolar cycloaddition of nonstabilized azomethine ylide: Formal total synthesis of (+/-)-pancracine - Pandey, Ganesh; Banerjee, Prabal; Kumar, Ravindra; Puranik, Vedavati G. (Organic Letters, 2005)
[GRAPHICS] The core structure of the complex pentacyclic 5,11-methanomorphanthridine alkaloids is constructed stereospecifically in one step employing an intramolecular [3 + 2]-cycloaddition of nonstabilized azomethine ylide as the key step. The strategy is demonstrated by accomplishing the formal total synthesis of (+/-)-pancracine.